Clinical and histopathological characteristics of soft tissue tumours at Hue University of Medicine and Pharmacy Hospital - Nguyen, Van Mao; Tran, Van Bao; Tran, Thi Nam Phuong; Tran, Nam Dong (Tạp chí Y Dược Huế, 2026)
ABSTRACT Background: Soft tissue tumors represent a relatively common and heterogeneous group of lesions characterized by diverse yet nonspecific clinical manifestations. Although histopathology remains the diagnostic gold standard, the application of advanced techniques such as immunohistochemistry is indispensable to ensure the accurate diagnosis with the latest WHO classification. Objectives: (1) To describe clinical characteristics and the histopathological classification of soft tissue tumors. (2) To evaluate the expression of immunohistochemical markers in soft tissue tumors. Materials and methods: A cross-sectional study was conducted on 166 patients diagnosed with soft tissue t umors between 04/2025 and 01/2026 at Hue University of Medicine and Pharmacy Hospital. Results: Malignant soft tissue tumors accounted for 21.1% of cases. The majority presented with a single lesion (91.6%), most commonly located in the superficial trunk (34.4%). Tumors smaller than 5 cm comprised 68.1% of cases. Adipocytic tumors were the most frequent (42.8%). Lipoma and hemangioma were predominant in the benign group (53,4% and 15,5%), fibrohistiocytoma in the borderline group (61,5%), and fibrosarcoma in the malignant group (22,7%). Immunohistochemistry revealed the expression of characteristic markers that supported the diagnostic classification, Vimentine (+) 100%, Desmine (+) 5/5 cases and SMA (+) 3/5 cases for smooth tumours, CD68 (+) 100% for fibrohistiocytic tumours, CD34 (+) for vascular and the other tumours.. Conclusion: Malignant soft tissue tumors accounted for 21.1% of cases. Besides histopathology, immunohistochemistry revealed the expression of characteristic markers that supported the key role for the classification of tumour types. Keywords: soft tissue tumours, histopathology, clinical characteristics, immunohistochemistry